Calculation of Spotting Particles Maximum Distance in Idealised Forest Fire Scenarios - José C. F. Pereira; José M. C. Pereira; André L. A. Leite; Duarte M. S. Albuquerque (Journal of Combustion)
Large eddy simulation of the wind surface layer above and within vegetation was conducted in the presence of an idealised forest fire by using an equivalent volumetric heat source. Firebrand’s particles are represented as spherical particles with a wide range of sizes, which were located into the combustion volume in a random fashion and are convected in the ascending plume as Lagrangian points. The thermally thin particles undergo drag relative to the flow and moisture loss as they are dried and pyrolysis, char-combustion, and mass loss as they burn. The particle momentum, heat and mass transfer, and combustion governing equations were computed along particle trajectories in the unsteady 3D wind field until their deposition on the ground. The spotting distances are compared with the maximum spotting distance obtained with Albini model for several idealised line grass or torching trees fires scenarios. The prediction of the particle maximum spotting distance for a 2000 kW/m short grass fire compared satisfactorily with results from Albini model and underpredicted by 40% the results for a high intensity 50000 kW/m fire. For the cases of single and four torching trees the model predicts the maximum distances consistently but for slightly different particle diameter.